2021
DOI: 10.3390/ijms222112025
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Tumor Immunogenicity Based Gene Signature for Skin Cancer Risk Stratification

Abstract: Melanoma is one of the most aggressive types of skin cancer, with significant heterogeneity in overall survival. Currently, tumor-node-metastasis (TNM) staging is insufficient to provide accurate survival prediction and appropriate treatment decision making for several types of tumors, such as those in melanoma patients. Therefore, the identification of more reliable prognosis biomarkers is urgently essential. Recent studies have shown that low immune cells infiltration is significantly associated with unfavor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Numerous studies have used differential gene expression analyses to compare metastatic and primary melanomas in order to identify prognostic markers [ 26 , 27 , 62 , 63 ]. Additionally, it has been reported that patients with low immune cell infiltration have poor clinical outcomes [ 27 , 64 , 65 , 66 ]. In our research, melanoma patients having “Ribosomal biogenesis” GES had the worst prognosis compared with the other identified GESs ( Figure 6 A,B,F) and showed a low level of immune cell enrichment ( Figure 4 D).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have used differential gene expression analyses to compare metastatic and primary melanomas in order to identify prognostic markers [ 26 , 27 , 62 , 63 ]. Additionally, it has been reported that patients with low immune cell infiltration have poor clinical outcomes [ 27 , 64 , 65 , 66 ]. In our research, melanoma patients having “Ribosomal biogenesis” GES had the worst prognosis compared with the other identified GESs ( Figure 6 A,B,F) and showed a low level of immune cell enrichment ( Figure 4 D).…”
Section: Discussionmentioning
confidence: 99%